PERLINDUNGAN HUKUM BAGI PASIEN TERHADAP KESALAHAN APOTEKER DALAM PEMBERIAN OBAT DI APOTEK GUNA MEDIKA - Dhella Tasya Putri; Ni Putu Noni Suharyanti (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2021)
Where the legal research was aimed to know consumers legal protection against errors of drug administration by pharmatics and to determine the legal arrangements for negligence in administering drugs by pharmatic to consumers. This legal writing is a normative research. Based on the result on the study, it can be concluded that the pharmatics responsibility arises when there is negligence in carrying out his profession as a relationship between pharamacis and patients in administering drug at the pharmacy. Based on Article 360 KUHP paragraph (1) and (2), the responsibility of pharmacist and pharmacist assistants is neligence that has been done in carrying out their pharmaceutical duties.